Proposed Marketing Strategy for Sharks Junior - Martin, Evan; Desiana, Krisnati (The Indonesian Journal of Business Administration, 2016)
Abstract. Fashion is one of the basic important necessities in our daily life. Nowadays children fashion form an important segment in the fashion retail industry and keep growing over the years. Sharks Junior was established in the middle of 2014 to answer the demand in the market for quality, affordable, street wear for kids, especially boys, aged 6-15 years old. Parents plays an important role in making decision for kids fashion because kids do notÂ  have the information and the purchasing power to purchase their own clothes. To attract these parents and boost sales, companies incorporate attractive promotions into their marketing strategies by using "High-Low" strategy. They will in the beginning, raise the original price of the products and offer high promotions in the same time, such as 50% discounts, discount up to 70% and Buy One Get One. Based on the condition above, author try to formulate the most suitable and effective marketing tools to build customer loyalty to Sharks Junior and increase sales without using "High-Low" strategy. Author conducted some surveys to collect objective data from consumers. The questionnaires were spread to parents in the department store and via online in attempt to get consumers perspectives about the brand, market, and products.Â Keywords: Sharks Junior, fashion, kids, sales, strategy, marketing